2019
DOI: 10.1364/ol.44.001484
|View full text |Cite
|
Sign up to set email alerts
|

Alignment-free dispersion measurement with interfering biphotons

Abstract: Measuring the dispersion of photonic devices with small dispersion-length products is challenging due to the phase-sensitive, and alignment-intensive nature of conventional methods. In this letter, we demonstrate a quantum technique to extract the second-, and third-order chromatic dispersion of a short single-mode fiber using a fiber-based quantum nonlinear interferometer. The interferometer consists of two cascaded fiber-based biphoton sources, with each source acting as a nonlinear beamsplitter. A fiber und… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…However, lowering losses and improving the quality of the aperiodic poling will provide an ultrabroadband phase measurement at a precision surpassing that of the interferometry with classical light. A similar recent experiment (16) reported a phase measurement in a band of 80 nm but in the low-gain regime, where at most one photon pair is produced for each pair of conjugated frequencies.…”
Section: Measurement Of the Phasementioning
confidence: 86%
See 1 more Smart Citation
“…However, lowering losses and improving the quality of the aperiodic poling will provide an ultrabroadband phase measurement at a precision surpassing that of the interferometry with classical light. A similar recent experiment (16) reported a phase measurement in a band of 80 nm but in the low-gain regime, where at most one photon pair is produced for each pair of conjugated frequencies.…”
Section: Measurement Of the Phasementioning
confidence: 86%
“…The aim of this article is to consider a nonlinear interferometer consisting of two aperiodically poled crystals placed into a common pump and generating broadband twin beams through high-gain PDC. The long-term motivation for considering this configuration is twofold: (i) measuring the broadband squeezing, produced by the first crystal (14), to determine the frequency band available for quantum operations, and (ii) measuring the phase shift introduced by a sample between the crystals in a wide band of frequencies (15,16). Our short-term objectives are building an analytic model of such an interferometer and observing the interference fringes as well as their displacement caused by the sample.…”
Section: Introductionmentioning
confidence: 99%
“…The biphotons generated in the cascade structure are sent to a dispersive medium (20 km of Corning SMF-28), which maps their wavelengths onto the arrival time at the single photon detectors 57 . After time-tagged detection with single photon detectors, the spectrum of the biphotons can be recovered by translating the time delays into wavelength 46,57 . The minimum resolution of our spectrometer depends primarily on the timing jitter of the single photon detectors 46 .…”
Section: Fiber Spectrometermentioning
confidence: 99%
“…On the other hand, the spontaneous regime of these interferometers has also been studied both theoretically 28,[35][36][37] , and experimentally [38][39][40][41] to investigate more abstract concepts such as "induced coherence" effect 38,[42][43] . These studies have since found their applications in measuring absorption 44 , refractive index 45 , and dispersion 46 of linear media.…”
Section: Introductionmentioning
confidence: 99%
“…Operating near the zero-dispersion wavelength of silica fiber, the time-correlated and polarization entangled biphotons generated in this source are expected to be robust against chromatic dispersion and polarization mode dispersion in long-distance quantum fiber communication [32][33][34]. Through further development, we anticipate that the source can be used in quantum applications such as wavelength-multiplexed quantum communication [19,35,36] and high precision quantum sensing [4,5,7,[37][38][39].…”
mentioning
confidence: 99%